Ecomuseu enquanto espaço de valorização do Patrimônio Cultural - RODRIGUES, Mirlana Emanuele Portilho (2024)
This dissertation adopts a broad perspective of cultural heritage. The approach seeks an interdisciplinary analysis, recognizing the diversity of perspectives in Social Sciences, Human Sciences and Natural Sciences, promoting a holistic and integrative view in research on Cultural and Natural Heritage. In view of the above, the research has the general objective of analyzing the Ecomuseum Sítio do Físico (Brazilian Name – in English Physicist's Site related to chief physicist – the place owner) based on the contributions of the museum institution through Environmental and Heritage Education. And as specific objectives: i. Understand how the Ecomuseum is framed as a museological proposal; ii. Discuss the potential of museum institutions (ecomuseum) as promoters of the preservation of cultural and environmental heritage; iii. Investigate how the Environmental and Heritage Education actions developed by the Ecomuseu Sítio do Físico occur and how they can contribute to promoting the memory and identity of the community where the museum institution is located. To achieve the objectives listed, the methodological path is a qualitative and interdisciplinary approach, using semi-structured interviews with the founders of the Sítio do Físico ecomuseum and some people from the community, who contribute to the ecomuseum or who benefit from the activities that the institution carries out. Data analysis was carried out using content analysis by Bardin (2011). As a result, the categories of Museum Management, Community Involvement and Educational Actions were identified and analyzed, which were important for understanding the functioning and impact of the Ecomuseu Sítio do Físico on the community in which it operates. Thus, a theoretical path is established based on the contributions of authors such as Bertotto. (2021), Graça Filipe and Hugues de Varine (2015), Davis (2019), Almeida (2013), Brulon (2015), Reis (2021), Tolentino (2013), Silva (2020), among others. After the analyses, the importance of the Ecomuseum Sítio do Físico stands out as an agent promoting the preservation, education and strengthening of the community's cultural and environmental identity. The museum institution demonstrates a commitment to integrating itself with social and environmental demands, maintaining a direct and collaborative link with the community.